Clinical trials corner: September 2017 - Rodrigues, Filipe Brogueira (2017)
© 2017 – IOS Press and the authors. All rights reserved. This article is published online with Open Access and distributed under the terms of the Creative Commons Attribution License (CC-BY 4.0).